STRATEGIES FOR EMPOWERMENT OF FOSTERED MICRO ENTERPRISES DURING THE PANDEMIC PERIOD AT THE OFFICE OF COOPERATIVES AND MICRO BUSINESSES IN SIDOARJO REGENCY - Regita Safiira Adina; Lukman Arif (DIA: Jurnal Administrasi Publik, 2021)
As a result of the Covid-19 pandemic that hit all countries including Indonesia, it has an impact on all business sectors including MSMEs. The condition of the Micro Businesses in the Sidoarjo Regency is not much different from the Micro Enterprises in other areas. The purpose of this research is to describe the Micro Business Empowerment Strategy Fostered during the pandemic at the Office of Cooperatives and Micro Enterprises, Sidoarjo Regency. The research method used in this research is the descriptive qualitative research method. The location of this research is in the Office of Cooperatives and Micro Enterprises, Sidoarjo Regency. The focus of this research is on the Strategy for Empowerment of Fostered Micro Enterprises in the Pandemic Period at the Office of Cooperatives and Micro Enterprises, Sidoarjo Regency. Sources of data used in this study are primary data and secondary data. Data collection techniques used in this study, namely observation, interviews, and documentation relating to existing information in the field. The results of the research can be said that the empowerment of Fostered Micro Enterprises during the pandemic carried out by the Sidoarjo Regency Cooperatives and Micro Enterprises has been running by following the applicable rules. And there is a need for better data collection for the Micro Businesses that exist in each sub-district in Sidoarjo Regency